التصميم الإنشائي لمبنى قصر المؤتمرات المقترح إنشاؤه في مدينة الخليل - سلامة, اياد; طميزي, محمد; الحموري, معاذ (جامعة بوليتكنك فلسطين - مباني, 2011)
لقد سعى الانسان منذ القدم الى تطوير اسلوب معيشته وكان السبب تطلعه لحياة جيدة ومريحة ورغبته في اقامة مشاريع تساعد على نمو اقتصادي سريع ، ومن هنا جاءت فكرة اقتراح انشاء قصر للمؤتمرات من اجل تحقيق هذه الاهداف وتكمن مشكلة البحث في ايجاد كافة الحلول الانشائية للتصميم المعماري الذي يحوي هذا المشروع ، وقد قمنا بعدة خطوات من اجل ايجاد الحلول تتمثل بداية بدراسة الموقع وملائمته للمشروع ، ومتابعة العمل بدراسة المخططات المعمارية ومن ثم البدء بالعمل الانشائي من دراسة لملائمة الهيكل المعماري للعمل الانشائي وتصميم كافة العناصر الانشائية التي يحويها المشروع بما فيها اعمدة وجسور وعقدات واعصاب وغيرها ، وبعد انهاء هذا العمل يجب ان نخلص الى عدد من النتائج المتوقعة من ربط للمعلومات وعمل كافة المخططات التنفيذية. Since the ever humans waited to develop the style of life and the reason behind that was to provide themselves a comfortable and decent life , and the desire to establish projects helps to get fast economic growth . And from above came the idea of suggesting to establish the conference palace , and the problem of this research is to find all the structural solutions to the architectural design which this project contains , we have a lot of steps to find solutions which represented in the beginning in the site plan studying and fitting it with the project , and continuing to study the rest of the architectural plans , then checking whether the architectural fitting with the structural work , and designing all the structural members in the project contained by the project including the columns , beams , slabs , and ribs , etc. And after finishing this side of the work , we had a conclusion to number of expected results which we reached through connecting information and doing the structural plans.
no of pages 127 , 12728 ,23/ مباني 2011 in the store
Keywords: التصاميم الانشائية; الابنية الثقافية; قصور المؤتمرات